2009
DOI: 10.1080/19368620902799643
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Web-Based Destination Marketing Activities: A Relationship Marketing Perspective

Abstract: This study aims to assess the Web-based destination marketing activities employed by American Convention and Visitors Bureaus (CVBs). Empirical data was collected via a survey from 260 CVBs in the USA. The research results reveal that organizational size, financial resources and management team's technological expertise are the dominating factors affecting the effective implementation of each of the four functions of Web-based marketing activities (i.e., information, communication, transaction, and assurance) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Thus, the need for further research on relationship marketing in the first-class and luxury hotel segment, especially in different geographical contexts in our view is very important and timely. A further review of the literature indicates that most of the studies on relationship marketing in the hospitality industry were conducted in the West (Bowen & Shoemaker, 1998;Campbell, Nicholsen, & Kitchen, 2006;Cobos et al, 2009;Fyall, Callod, & Edwards, 2003) and recently Asia (Kim, Han, & Lee, 2001;Sin, Tse, Chan, Heung, & Yim, 2006). Our literature search indicates that there was no study on relationship marketing practices in the hospitality industry in Ghana even though recent events indicate that the sector is highly competitive.…”
Section: Introductionmentioning
confidence: 78%
“…Thus, the need for further research on relationship marketing in the first-class and luxury hotel segment, especially in different geographical contexts in our view is very important and timely. A further review of the literature indicates that most of the studies on relationship marketing in the hospitality industry were conducted in the West (Bowen & Shoemaker, 1998;Campbell, Nicholsen, & Kitchen, 2006;Cobos et al, 2009;Fyall, Callod, & Edwards, 2003) and recently Asia (Kim, Han, & Lee, 2001;Sin, Tse, Chan, Heung, & Yim, 2006). Our literature search indicates that there was no study on relationship marketing practices in the hospitality industry in Ghana even though recent events indicate that the sector is highly competitive.…”
Section: Introductionmentioning
confidence: 78%
“…This view is corroborated by Chen and Yen (2004) who suggest that reciprocity between firms and their customers online is the most prominent element of interactivity. Thus, firms use online tools such as e-mails to promote interactivity through frequent communication between themselves and their customers, in the form of responses, questions, comments, feedback and criticisms (Fang, 2012;Cobos et al, 2009). Per Jeon et al 2016, perceived website interactivity plays a critical role in inciting positive behavioral intentions among customers online.…”
Section: Interactivitymentioning
confidence: 99%
“…A study conducted by Grove and Fisk (2001) concluded that limited resources, lack of communication, lack of proper management, employees insufficient knowledge, legal regulations and restrictions and ownership issues were the most important barriers to marketing innovation. Similarly, Cobos et al. (2009) and Essawy (2011) found that a successful Web marketing strategy is influenced by organisational and environmental factors.…”
Section: Introduction and Rationalementioning
confidence: 94%
“…Broadly speaking, hotels with adequate financial resources will be better prepared for relationship marketing implementation. For example, the studies of Cobos et al (2009) and Lee (2004) reveal a positive relationship between financial slack and the adoption of Internet marketing. This argument could be applicable to the case of independent Egyptian hotels.…”
Section: Organisational and Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation